Researching progress on bio-reactive electrogenic materials with electrophysiological activity for enhanced bone regeneration - Dong, Shaojie; Zhang, Yuwei; Mei, Yukun; Zhang, Yifei; Hao, Yaqi; Liang, Beilei; Dong, Weijiang; Zou, Rui; Niu, Lin (Frontiers in Bioengineering and Biotechnology, 2022)
Bone tissues are dynamically reconstructed during the entire life cycle phase, which is an exquisitely regulated process controlled by intracellular and intercellular signals transmitted through physicochemical and biochemical stimulation. Recently, the role of electrical activity in promoting bone regeneration has attracted great attention, making the design, fabrication and selection of bioelectric bioreactive materials a focus. Under specific conditions, piezoelectric, photoelectric, magnetoelectric, acoustoelectric and thermoelectric materials can generate bioelectric signals similar to those of natural tissue and stimulate osteogenesis-related signaling pathways to enhance the regeneration of bone defects, which can be used for designing novel smart biological materials for engineering tissue regeneration. However, literature summarizing studies relevant to bioelectric materials for bone regeneration is rare to our knowledge. Consequently, this review is mainly focused on the biological mechanism of electrical stimulation in the regeneration of bone defects, the current state and the future prospects of piezoelectric materials and other bioelectric active materials suitable for bone tissue engineering in recent studies, aiming to provide a theoretical basis for novel clinical treatment strategies for bone defects.